The Role of The Police as Law Enforcement Officers in Handling Cases of Criminal Acts of Domestic Violence (KDRT) Against Women as Victims Based on A Normative Juridical Basis - Sella Romantika (Proceedings Series on Social Sciences & Humanities, 2023)
Domestic violence against women is a serious and dangerous form of human rights violation. The police as law enforcement officers play an important role in handling domestic violence cases, including protecting women victims and providing justice for them. This research examines a brief overview of the role of the police in handling domestic violence cases against women victims, as well as the challenges faced in carrying out their duties with reference to UU No. 23 of 2004. This includes the initial response to the victim's report, careful investigation, collection of evidence, and arrest of the perpetrator. The police as one of the units of the police apparatus responsible for law enforcement has a duty to implement upright laws such as conducting investigations and providing protection for victims of violence in domestic violence. The police are at the forefront in handling domestic violence cases, namely by enforcing the law as stipulated in Article 13 of Law No. 23 of 2002 concerning the police of the Republic of Indonesia. The research conducted is normative juridical research, namely by examining legislation, literature in accordance with the problems studied.